Mediadores: problematizando algumas trajetórias - Arnaldo José Zangelmi; Fabrício Roberto Costa Oliveira; Izabella Fátima Oliveira de Sales (Ciências Sociais Unisinos)
This article aims to discuss the main outlines of the trajectories of individuals recognized as mediators, trying to analyze the main factors that influenced the formation of skills and interests for that specific action. Thus, we intend to identify alternatives to analyses that emphasize the metropolitan environment as a privileged locus for training mediators, based on some trajectories of members of social movements.